Adjustment Challenges Faced by Freshmen in Transition from School to University in Azerbaijan : Investigating the Role of Extracurricular Activities - Huseynzada, Aytan (ADA University, 2022)
The transition from school to university is an unavoidable step for students, there is a possibility of experiencing challenges during that process. However, the role of extracurricular activities in overcoming those challenges is one of the concerning issues in education. This study aimed to explore the role of extracurricular activities during a transition process among students’, instructors’, and administrators’ perspectives in two higher educational institutions (HEIs) in Azerbaijan. The researcher intended to explore how research participants perceived the period of transition and how they consider the role of extracurricular activities in suspending those problems. Previous research relied on quantitative research analysis only, but for this study was chosen mixed-method research. The conceptual framework of this study was based on three theories: The Social Learning Theory by Bandura (1992), an Acculturation Model by Berry (1980), and the Ecological Systems theory by Bronfenbrenner (1994). The instruments of the research for qualitative analysis were semi-structured interviews, but for quantitative was a survey with 164 student participants. Four freshmen, two instructors teaching freshmen, and two administrators dealing with extracurricular activities were the target population for interviews from two higher educational institutions (HEIs), specifically one private and a public university chosen based on a convenience sampling) in Azerbaijan. The major findings of this study showed students were experiencing transition challenges such as insomnia, anxiety, stress, etc. However, less than half of the survey participants did not consider extracurricular activities as a way of overcoming those challenges. Moreover, based on interview responses, two interpretations emerged about the role of extracurricular activities. The researcher suggests that further research is important to consider students’ background in explaining those difficulties faced by students. Furthermore, students might be surveyed about what extracurricular activities they might find appealing to be engaged in. The researcher recommends administrators develop career-based extracurricular activities by encouraging not only students but also instructors. Moreover, creating workshops and training for giving some practical knowledge about the purpose of extracurricular activities to the university administrators.
Keywords: Education, Higher -- Azerbaijan.; Education, Higher -- Freshmen.; Education, Higher -- Freshmen -- Challenges.; Education